Answer:
see explanation
Explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
To calculate m use the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
3
Using (x₁, y₁ ) = (0, 0) and (x₂, y₂ ) = (- 3, 6)
m =
=
= - 2
Since the line passes through the origin (0, 0) then y- intercept is 0
y = - 2x ← equation of line
4
let (x₁, y₁ ) = (6, 0) and (x₂, y₂ ) = (0, 3)
m =
=
= -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
note the line crosses the y- axis at (0, 3) ⇒ c = 3
y = -
x + 3 ← equation of line
5
let (x₁, y₁ ) = (0, 3) and (x₂, y₂ ) = (-2, - 3)
m =
=
= 3
note the line crosses the y- axis at (0, 3) ⇒ c = 3
y = 3x + 3 ← equation of line